2004
DOI: 10.1207/s15374424jccp3301_15
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Parental Coping Styles and Parent-Child Interactions Before and After Treatment for Children With ADHD and Oppositional Behavior

Abstract: This study examined the relation between parental coping styles, discipline, and child behavior before and after participating in a parent training program for parents of children with Attention-Deficit/Hyperactivity Disorder (ADHD) and oppositional behavior. For mothers, use of more maladaptive and less adaptive coping styles was related to more self-reported lax and overreactive discipline, more observed coercive parenting, and more observed child misbehavior prior to parent training. No significant relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 48 publications
4
34
0
1
Order By: Relevance
“…The stress that parents experienced and the negative coercive/avoidant way that they dealt with the challenging situations are also consistent with the literature that indicates that parenting a child with AD/HD is stressful and overwhelming and that these parents have more negative and coercive parenting practises (Daley et al 2003;McKee et al 2004;Gerdes & Hoza 2006;Graziano et al 2011;Kendall 1998;Lewis-Abney 1993;Murphy & Barkley 1996;Theule et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…The stress that parents experienced and the negative coercive/avoidant way that they dealt with the challenging situations are also consistent with the literature that indicates that parenting a child with AD/HD is stressful and overwhelming and that these parents have more negative and coercive parenting practises (Daley et al 2003;McKee et al 2004;Gerdes & Hoza 2006;Graziano et al 2011;Kendall 1998;Lewis-Abney 1993;Murphy & Barkley 1996;Theule et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Psychogiou, Daley, Thompson, and Sonuga-Barke (2007) suggested that the increased probability of oppositional problems for children with ADHD can be attributed to the bidirectional nature of complex parent-child interactions. Also, studies have shown that parents of children with ADHD respond to the stress brought on by their child's behavior with inappropriate or ineffective parenting (McKee, Harvey, Danforth, Ulaszek, & Friedman, 2004).…”
Section: Parenting Behaviorsmentioning
confidence: 99%
“…Also, found that distressed mothers were inclined to demonstrate an aversive attitude and harsh discipline in order to manage children's problem behavior. Finally, maladaptive parent coping strategies are associated with ineffective parenting behaviors ranging from coercive (harsh/punitive) to lax (inconsistent/ignoring) discipline (McKee et al 2004). While the relations between poverty, parent stress and parenting practices, and child psychopathology are robust, more investigation is needed in order to generalize these findings to Chinese populations.…”
Section: Parenting Practices and Copingmentioning
confidence: 99%